Resolusi Fiqh Indonesia: Antara Konsep dan Realitas (Studi Analisis terhadap Pemberlakuan Fiqh di Indonesia) - Wasik, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Fiqh is a product and the result of ijtihad of the Imams whose sources are taken from the Qur'an and Al-Hadith. However, Fiqh is elastic and dynamic in its application. Its Asbabun Nuzul and Asbabul Wurud in Mecca and Medina are very different in their situation and condition with Indonesia. Thus, fiqh legal products that were born at the time were of course also different from fiqh products that appeared in Indonesia. One of the causes is the social interaction and the existing situation and condition, so that the legal product of fiqh is also different